2018
DOI: 10.1186/s12931-018-0885-x
|View full text |Cite
|
Sign up to set email alerts
|

Elevated serum soluble programmed cell death ligand 1 concentration as a potential marker for poor prognosis in small cell lung cancer patients with chemotherapy

Abstract: BackgroundPotential relationship between serum soluble programmed cell death ligand 1 and prognosis of small cell lung cancer is not well explored. The aim of the study was to reveal the prognostic significance of serum soluble programmed cell death ligand 1 in patients with small cell lung cancer.MethodsA total of 250 small cell lung cancer patients and 250 controls were included. Research information was obtained from their medical records. Blood samples were collected on admission. Serum concentration of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 44 publications
(45 reference statements)
0
11
0
Order By: Relevance
“…One study was excluded for cases less than 20 ( 38 ). Two studies focusing on small-cell lung cancer ( 39 ) and lung carcinomas ( 40 ) were excluded. Finally, eight studies ( 20 , 41 47 ) were included in this study.…”
Section: Resultsmentioning
confidence: 99%
“…One study was excluded for cases less than 20 ( 38 ). Two studies focusing on small-cell lung cancer ( 39 ) and lung carcinomas ( 40 ) were excluded. Finally, eight studies ( 20 , 41 47 ) were included in this study.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of patients are diagnosed with metastatic diseases at the initial visit, which highlights the importance of effective systemic therapies (3). The traditional therapy is chemotherapy, and certain gene expression patterns (4,5) and liquid biomarkers (6,7) serve as predictors of chemotherapy outcomes. Targeted therapy with small molecule tyrosine…”
Section: Introductionmentioning
confidence: 99%
“…In the subgroup analysis of patients receiving immunotherapy, patients with high sPD-L1 levels were correlated with a worse OS. An NSCLC study showed that the death risk in patients with high levels of sPD-L1 was 2.68 (95%CI 1.36–5.28) times the risk in patients with low sPD-L1 levels ( 14 ). Given that sPD-L1 can be derived from tumor tissue cells, the level of sPD-L1 can reflect tumor regression to a certain extent.…”
Section: Discussionmentioning
confidence: 99%